Application of The Contextual Teaching and Learning (CTL) Model in Improving The Quality of Balaghah Learning in MAN 3 Jombang - Muhammad Afthon Ulin Nuha; Nurul Musyafa’ah (Jurnal Ilmiah Iqra', 2023)
In Indonesia, the problem that often arises in learning is that students' understanding of the material is still low, as evidenced by student learning outcomes that are still low. This is certainly not caused by the common knowledge of students alone. Still, many factors that influence one of them are the learning process that is less qualified, human resources in the form of unprofessional teachers so that students' abilities will also be low. If this continues, the output of human resources resulting from learning in Indonesia will not be able to compete with countries that are both developing. This study aims to reveal in more depth the application of the contextual teaching and learning (CTL) learning model in improving the quality of Balaghah learning at MAN 3 Jombang, with the focus of the discussion as follows 1) Planning of Contextual Teaching and Learning (CTL) models in improving the quality of Balaghah learning at MAN 3 Jombang, (2) the quality of Balaghah learning as the output of the application of the Contextual Teaching and Learning (CTL) model at MAN 3 Jombang. This research uses a qualitative approach, with the type of case study research in schools. Data collection was done by interview, observation, and documentation. Data analysis was done through data reduction, presentation, and conclusion. The results of this study are 1) Planning the Contextual Teaching and Learning (CTL) Model, there are three stages; first, the introduction is to see the suitability of essential competencies with methods, materials, models, media, and learning resources. Second, implementation is the student centre learning process through several stages of learning. Third, the teacher evaluates the students. 2) The quality of Balaghah learning as the output of applying the Contextual Teaching and Learning (CTL) model at MAN 3 Jombang is related to teacher learning behaviour, student learning behaviour, impact, learning climate, learning materials, and learning media